Neuropsychiatric systemic lupus erythematosus: a rare case of acute polyneuropathy - Anand, Aditya; Siddiqui, Ammar S.; Singh, Shivam; Basera, Pragati (International Journal of Research in Medical Sciences, 2023)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which presents most commonly in middle aged females and affects multiple organ systems. Amongst the many systems involved, the nervous system generally gets affected later in the course of the disease. We report a case of a male patient who developed quadriparesis as the initial presentation of SLE who progressed to lupus nephritis. The patient was started on methylprednisolone, and later planned on IVIg when he did not respond to the initial treatment. Unfortunately, the patient developed diaphragmatic paralysis and succumbed to the illness.